2016
DOI: 10.1159/000444219
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Barrier Creams against Irritant Contact Dermatitis

Abstract: Introduction: Skin tissue is frequently exposed to various irritant substances in the workplace, particularly in wet work, which can lead to the development of occupational contact dermatitis. ‘Barrier' creams (BCs) are well known, and their applications are still the subject of many studies and controversies. Methods: We searched all controlled trials investigating BCs against cutaneous irritants in humans published between 1956 and December 2014 from MEDLINE, PubMed, reference lists and existing reviews. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Practical literature‐based recommendations referring to this are summarized in Table 6. Regarding barrier creams, evidence for their efficacy 65,66 is limited. They may only be effective against certain irritants and may sometimes even intensify the irritant skin response 67–69 .…”
Section: Preventionmentioning
confidence: 99%
“…Practical literature‐based recommendations referring to this are summarized in Table 6. Regarding barrier creams, evidence for their efficacy 65,66 is limited. They may only be effective against certain irritants and may sometimes even intensify the irritant skin response 67–69 .…”
Section: Preventionmentioning
confidence: 99%
“…Thus, development of allergic CD skin lesions includes complex immune pathways, influenced by both genetic and environmental triggers ( 14 ). There are prominent roles of genetic variations and mutations (predominantly filaggrin mutations) and impaired barrier function (e.g., aberrancies in epidermal pH buffering capabilities), which may promote bacterial biofilms and create an environment favoring sensitization ( 13 , 22 , 23 ). Regarding genetics, according to research data, filaggrin mutations (R501X, 2282del4, and R2447X) were identified in 16.9% of patients with hand eczema and were significantly associated with skin lesions (skin fissures on the fingers and heels).…”
Section: The Pathomechanisms Of Contact Dermatitismentioning
confidence: 99%
“…. Barrier creams have demonstrated effectiveness in maintaining skin hydration and providing protection against skin barrier damage caused by irritants . By restoring the disrupted skin barrier, barrier creams, such as the one tested in the current study, can break the cycle of epidermal damage in incontinent patients and allow healing of the skin and reduction in IAD .…”
Section: Section 4: the Use Of A Dermo‐cosmetic Product Containing Rhmentioning
confidence: 94%